Multicriteria decision analysis applied to the spatial allocation of crops as a planning support system for agricultural expansion in Brazil - Alkimim, Akenya Freire de (2014)
The history of the advancement of the agricultural frontier in Brazil has been closely related to environmental losses. Although environmental losses are sometimes inevitable in the context of agricultural expansion, they should always be minimized. This study seeks to avoid the past pattern of development by proposing a more sustainable way of expanding agriculture. The research tests whether it is possible to expand the cultivation of food and fuel crops in Brazil without compromising natural ecosystems. Brazil has a great agricultural potential considering the significant amount of lands that is suitable for agriculture with a favorable climate and topography. To supply the domestic agricultural market and for Brazil to take on a global food and biofuel export leadership position, actions should be taken to plan for this potential sustainable expansion. This planning would be an alternative means of advancing the agricultural frontier, as opposed to the deforestation previously practiced. A way to accomplish a sustainable pattern of agricultural development could be by the identification of suitable areas to support the expansion without further loss of forestlands. Pasture is a type of land use that occupies large areas in Brazil, and pastures are considered strategic resources for the effectiveness of the proposed expansion, given that they represent areas that have already been deforested and offer some type of existing infrastructure. In addition, from the current biophysical potential production - pasture based beef cattle - may be underused. The goal of this dissertation is to develop a spatial allocation model based on a multicriteria decision making and geographic information systems (GIS) using land suitability analysis to support decision makers with geospatial information about where potential areas for sugarcane and soybean expansion are located in Brazil. The multicriteria decision analysis (MCDA) consists of physical land suitability, infrastructure and socioeconomic data integration to identify suitable pasturelands for crop allocation. To enhance the reliability of the model, a team of specialists in the agricultural crops was selected to establish the criteria priorities in the model for the analysis process. The combination of their judgments gives an overall priority that feeds the multicriteria model. \"What if\" scenarios were also built to show how changes in the criteria priority weights would modify the spatial distribution of suitability classes in relation to the main model. The results yield maps that represent the distribution of suitability classes for sugarcane and soybean expansion. Pasturelands become more or less suitable for sugarcane or soybean allocation according to shifts in the influence of each criterion in the model. The designed models show results that may assist policymakers with geospatial information about priority areas where investments and efforts should be directed for sustainable agricultural expansion in Brazil.